2012
DOI: 10.1007/978-94-007-5179-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Use of 113Cd NMR to Probe the Native Metal Binding Sites in Metalloproteins: An Overview

Abstract: Our laboratories have actively published in this area for several years and the objective of this chapter is to present as comprehensive an overview as possible. Following a brief review of the basic principles associated with 113Cd NMR methods, we will present the results from a thorough literature search for 113Cd chemical shifts from metalloproteins. The updated 113Cd chemical shift figure in this chapter will further illustrate the excellent correlation of the 113Cd chemical shift with the nature of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 174 publications
2
31
0
1
Order By: Relevance
“…[11,12] Structure-interfering properties of Cd II bindingt oZ n IIcontaining proteins remain controversial because ford ecades Cd II was used as aZ n II -isostructural spectroscopic probe for Zn II -binding proteins in UV spectrophotometric studies and 113 Cd NMR spectroscopy. [13][14][15][16][17] Although Cd II and Zn II ionicr adii are relatively similar and displacementi su sually one-to-one, in terms of stoichiometry and coordination sphere, their binding to at arget protein could potentially generate ad ifferent structural outcome. The presented scientific problem of Zn II -to-Cd II substitution and its impact on zinc-binding proteins have been extensively studied;h owever,a ll published data are focused on intramolecular sites, mostly of zinc finger domains and metallothioneins.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Structure-interfering properties of Cd II bindingt oZ n IIcontaining proteins remain controversial because ford ecades Cd II was used as aZ n II -isostructural spectroscopic probe for Zn II -binding proteins in UV spectrophotometric studies and 113 Cd NMR spectroscopy. [13][14][15][16][17] Although Cd II and Zn II ionicr adii are relatively similar and displacementi su sually one-to-one, in terms of stoichiometry and coordination sphere, their binding to at arget protein could potentially generate ad ifferent structural outcome. The presented scientific problem of Zn II -to-Cd II substitution and its impact on zinc-binding proteins have been extensively studied;h owever,a ll published data are focused on intramolecular sites, mostly of zinc finger domains and metallothioneins.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization estimates that 2.9 million deaths per year are attributable to diabetes, and this number is likely to increase by more than 50% in the next decade [1]. Much of this burden may be explained by the dramatic rise in obesity rates [2].…”
Section: Introductionmentioning
confidence: 99%
“…15 In this work, we investigated the effect of Cd 2+ on the structure and membrane-binding properties of the C2 domain from protein kinase Cα (C2α). Unexpectedly, we found that despite high affinity of Cd 2+ to C2α and the similar coordination geometry of protein-bound Cd 2+ and Ca 2+ , Cd 2+ is unable to support the membrane-binding function of the protein.…”
mentioning
confidence: 99%